Correlation Between Teamwork and Patient Safety in a Tertiary Hospital in Cyprus - Kyriacou Georgiou, Mary; Merkouris, Anastasios; Hadjibalassi, Maria; Sarafis, Pavlos; Kyprianou, Theodoros (My University, 2021)
Background Over time, the multidimensional nature of the safety culture in the healthcare field has led to great efforts to improve quality and create tools aiming at enhancing safety. In particular, emphasis has been placed on teamwork and the safety climate. There is a strong relationship between these two complex elements, which interact to improve the safety climate and reduce patient-safety issues. In this study, "teamwork" includes the perceptions of the health professionals collaborating within a health team to provide safe patient care, and "safety climate" refers to the professional commitment to patient safety. Objective This article assesses health professionals' perceptions of both patient-safety issues and teamwork in their hospital work environment after the development and implementation of a comprehensive quality-assurance system. Methods This descriptive correlation study is based on anonymous and self-completed questionnaires obtained after the development and implementation of a comprehensive quality assurance system in the wards and departments of Nicosia General Hospital. The research sample consisted of the health professionals who participated in the working groups that implemented the quality assurance system. We used the questionnaire's sociodemographic data and the Safety Attitudes Questionnaire (SAQ) developed in the Deepening our Understanding of Quality Improvement in Europe program, focusing on two factors: Teamwork and the safety climate. Results While teamwork received a positive score (>75%), the same did not occur for the safety climate (68.60%). Women typically rated the safety climate more positively than men, who mostly gave negative ratings (p = 0.005). There was a statistically significant difference (p = 0.011) in the scores between participants aged 24-44 and those aged 45-54, with the latter reporting higher teamwork scores. The participants' educational levels also played important roles in their responses, with university graduates (BSc) providing more positive teamwork scores than those with a master's degree (p = 0.018). Conclusions Our research revealed that the health professionals of Nicosia General Hospital perceived the teamwork climate as positive, in contrast to the safety climate. The results highlight the need not only to intervene in all the areas covered by the SAQ to improve the safety climate but also to keep encouraging teamwork to obtain better results.
Keywords: Deepening our understanding of quality improvement in europe; Safety attitudes questionnaire; Hospitals; Health professionals; Teamwork; Safety climate